Partnerships in Mitigating Climate Change Impacts: a Case Study of the Mera Program - Cintya Dian Astuty; Maria R. Nindita Radyati (Journal of World Science, 2024)
This research aims to analyze partnerships in mitigating the impacts of climate change through the MERA Program in Muara Angke Wildlife Sanctuary, North Jakarta, which runs from 2018 to 2020. The method used is descriptive qualitative with data collection techniques through interviews, observations, and documentary studies. The results showed that the MERA Program successfully integrated multi-stakeholder partnerships in mangrove ecosystem restoration. The resulting positive impacts include economic benefits, treatment, natural disaster mitigation, and carbon reduction in the region. The program also significantly contributes to the achievement of various Sustainable Development Goals (SDGs), such as no poverty, no hunger, decent work, economic growth, sustainability, climate action, life under water, life on land, and partnership to achieve goals. The implication of this research is the importance of strengthening partnerships in efforts to mitigate the impacts of climate change through a holistic ecosystem restoration program that involves various stakeholders. The implication of this research is the importance of strengthening partnerships in efforts to mitigate the impacts of climate change through a holistic ecosystem restoration program that involves various stakeholders.